Аналіз актуальності розробки платформи з продажу косметичних засобів з точки зору користувача - Россохач, К. О. (ХНУРЕ, 2023)
The development of e-commerce in the field of cosmetics has been very active in recent years. According to research, the demand for cosmetics on the Internet is growing every year. However, this process may not be entirely comfortable for users, which makes the issue of developing a convenient online store selling cosmetics relevant.